Mechanism of Enhanced Oral Absorption of a Nano-Drug Delivery System Loaded with Trimethyl Chitosan Derivatives - Zhao Y; Lin S; Fang R; Shi Y; Wu W; Zhang W; Chen H (International Journal of Nanomedicine, 2022)
Ying Zhao,1,* Shiyuan Lin,1,2,* Ruiyue Fang,1 Yaling Shi,1 Wei Wu,1 Wei Zhang,1 Hui Chen1 1College of Pharmacy, Guilin Medical University, Guilin, 541199, People’s Republic of China; 2Science and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou, 510405, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui Chen; Wei Zhang, College of Pharmacy, Guilin Medical University, No. 1 Zhiyuan Road, Guilin, 541199, People’s Republic of China, Email chenhui_gl@163.com; 22437564@qq.comIntroduction: In the previous study, nanoparticles coated with trimethyl chitosan (TMC) derivatives (PPTT-NPs) could promote the oral bioavailability of panax notoginseng saponins (PNS). Herein, we chose PPTT-NPs as a model drug to study the property and mechanism of intestinal absorption in vitro and in vivo.Methods: The stability of PPTT-NPs was evaluated using simulated gastric fluid and simulated intestinal fluid. The uptake and transport of PPTT-NPs were investigated in Caco-2 and Caco-2&HT29 co-culture cells. The biosafety, intestinal permeability, adhesion, and absorption mechanism of PPTT-NPs were investigated using SD rats in vivo. The live imaging and biodistribution of PPTT-NPs were observed by IVIS. Furthermore, the effects on CYP3A4 of PPTT-NPs were investigated using testosterone as the probe substrate.Results: The results of the stability assay showed that PPTT-NPs had a strong tolerance to the pH and digestive enzymes in the gastrointestinal environment. In vitro cell experiments showed that the uptake of drugs exhibited a time-dependent. When the ratio of TMC-VB12 and TMC-Cys was 1:3, the uptake capacity of PPTT-NPs was the highest. PPTT-NPs could enhance the paracellular transport of drugs by reversibly opening a tight junction. Animal experiments demonstrated that PPTT-NPs have good biological safety. PPTT-NPs had good adhesion and permeability to small intestinal mucosa. Meanwhile, PPTT-NPs needed energy and various protein to participate in the uptake of drugs. The live imaging of NPs illustrated that PPTT-NPs could prolong the residence time in the intestine. Moreover, TMC-VB12 and TMC-Cys could reduce the metabolism of drugs by inhibiting CYP3A4 to a certain extent.Conclusion: The results show that TMC-VB12 and TMC-Cys are effective in the transport of PPTT-NPs. PPTT-NPs can increase the intestinal adhesion of drugs and exert high permeation by intestinal enterocytes which demonstrate significant and efficient potential for oral delivery of the BCS III drugs.Graphical Abstract: Keywords: Panax notoginseng saponins, TMC derivatives, nanoparticles, oral absorption, Caco-2&HT29 co-culture cells